Advertising e-government services in Kazakhstan: status, international experience and development opportunities - Yesbergen, R.A. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the need for advertising of electronic public services in the city of Aktobe of the Republic of Kazakhstan in the framework of the project of the grant financing of research projects of the Academy of Public Administration under the President of the Republic of Kazakhstan. The purpose of the scientific article is the scientific substantiation of the effectiveness of the use of advertising as a means of promotion to stimulate the population in obtaining electronic public services in terms of digitalization. The scientific article analyzes the directions of the administrative reform to ensure the quality and availability of public services and features of the development of electronic public services. A review of foreign experience of increasing public demand for e-government services was made. Also the features of advertising electronic public services, effective tools, global trends in public service advertising are considered. When writing this article, we used scientific methods such as the method of scientific abstraction, the method of economic analysis and synthesis, the static method, the macroeconomic method, the method of comparison. The main conclusions and proposals of the scientific article are based on the laws of the Republic of Kazakhstan on the development of electronic government and improving the quality of public services, on the Annual Messages of the President of the Republic of Kazakhstan and on the state program «Digital Kazakhstan».